A Distributed Architecture for Norm-Aware Agent Societies - García-Camino, A.; Rodríguez-Aguilar, J. A.; Sierra, C.; Vasconcelos, W. (Declarative Agent Languages and Technologies III, 2006)
We propose a distributed architecture to endow multi-agent systems with a social layer in which normative positions are explicitly represented and managed via rules. Our rules operate on a representation of the states of affairs of a multi-agent system. We define the syntax and semantics of our rules and an interpreter; we achieve greater precision and expressiveness by allowing constraints to be part of our rules. We show how the rules and states come together in a distributed architecture in which a team of administrative agents employ a tuple space to guide the execution of a multi-agent system.